Peptoniphilus gorbachii alleviates collagen-induced arthritis in mice by improving intestinal homeostasis and immune regulation - Kim, Suhee; Chun, Sung Hak; Cheon, Yun-Hong; Kim, Mingyo; Kim, Hyun-Ok; Lee, Hanna; Hong, Seong-Tshool; Park, Sang-Jun; Park, Myeong Soo; Suh, Young Sun; Lee, Sang-Il (Frontiers in Immunology, 2024)
The intricate connection between gut microbiota and rheumatoid arthritis (RA) pathogenesis has gained prominence, although the specific microbial species contributing to RA development remain largely unknown. Recent studies have sought to comprehensively explore alterations in the human microbiome, focusing on identifying disease-related microbial species through blood analysis. Consequently, this study aimed to identify RA-associated microbial species using a serum microbial array system and to investigate the efficacy and underlying mechanisms of potential microbial species for RA treatment.Methods: Serum immunoglobulin M levels against 384 intestinal microbial species were assessed using a microbial microarray in patients with RA and healthy individuals. We investigated the therapeutic potential of the identified microbial candidate regarding arthritis development, immune responses, gut barrier function, and gut microbiome using a collagen-induced arthritis (CIA) mouse model.Our findings revealed significant alterations in antibody levels against 36 microbial species in patients with RA compared to healthy individuals. Notably, the antibody levels against Peptoniphilus gorbachii (PG) were decreased in patients with RA and exhibited an inverse correlation with RA disease activity. In vitro experiments demonstrated that PG produced acetate and butyrate, while exhibiting anti-inflammatory properties. In CIA mice, PG administration suppressed arthritis symptoms, reduced the accumulation of inflammatory monocytes in the mesenteric lymph nodes, and downregulated gene expression of pro-inflammatory cytokines in the ileum. Additionally, PG supplementation restored intestinal barrier integrity and partially resolved gut microbial dysbiosis in CIA mice. The fecal microbiota in PG-treated mice corresponded to improved intestinal barrier integrity and reduced inflammatory responses.3 Conclusion: This study highlights the potential of serum-based detection of anti-microbial antibodies to identify microbial targets at the species level for RA treatment. Moreover, our findings suggest that PG, identified through the microbial microarray analysis, holds therapeutic potential for RA by restoring intestinal barrier integrity and suppressing the immunologic response associated with RA.